6x+87=11x-13

Simple and best practice solution for 6x+87=11x-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+87=11x-13 equation:


Simplifying
6x + 87 = 11x + -13

Reorder the terms:
87 + 6x = 11x + -13

Reorder the terms:
87 + 6x = -13 + 11x

Solving
87 + 6x = -13 + 11x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11x' to each side of the equation.
87 + 6x + -11x = -13 + 11x + -11x

Combine like terms: 6x + -11x = -5x
87 + -5x = -13 + 11x + -11x

Combine like terms: 11x + -11x = 0
87 + -5x = -13 + 0
87 + -5x = -13

Add '-87' to each side of the equation.
87 + -87 + -5x = -13 + -87

Combine like terms: 87 + -87 = 0
0 + -5x = -13 + -87
-5x = -13 + -87

Combine like terms: -13 + -87 = -100
-5x = -100

Divide each side by '-5'.
x = 20

Simplifying
x = 20

See similar equations:

| x-11=4+6x | | 2y+6=3y+4 | | (y-11)-(y+10)=6y | | 5+4x=9x | | 88(-22x-23)=25(-55x+11) | | 185-6=6x+5 | | 100*(x*x)+900x=414000 | | 3(-1.14+5)-1.14=5(1-1.14)+2 | | 5y-9+y+55=6y+50-2y | | 6x=16+8x | | y=-6x+21 | | 2978x+83=12 | | X^2=506.25 | | -20+4x=-6x | | 1/x+1+2=5/x+1 | | 180=2(24)+2w | | 3x+28=10x+10 | | (4v^3x^6)/(6u^2v^5-4v^2) | | d/10 | | 2(x-3)+5y=2y+4 | | (4v^3x^6)/6u^2v^5-4v^2 | | g^2-26g=23 | | .06x+.09(6000x)= | | -9x+6y=192 | | .75b+88=163 | | -7+8x=19+15 | | -9+4y=41 | | m^2+16m+27=0 | | p^2+18p=17 | | 5/12+112/12-3+3d+7-42 | | q^2+16q-225=0 | | f(x)=-x^2+14x-47 |

Equations solver categories